ANALISIS LITERASI SISWA KELAS IV KOTA DEMAK MELALUI MEDIA KOMIK BERORIENTASI PROFIL PELAJAR PANCASILA - Muhammad Eko Munandar Rifki; Intan Rahmawati; Lina Putriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main issue in the field of education today lies not only in students' lowacademic achievement but also in their lack of reading interest, which directlyaffects their literacy skills. This problem is also evident at SDN Karangsono 3 inDemak Regency, particularly among fourth-grade students who show lowenthusiasm for reading activities and have not yet utilized the school's literacyresources effectively. To address this issue, the study aimed to examine students’reading literacy skills through the use of comics that incorporate the values of thePancasila Student Profile and to analyze the effectiveness of this medium. Theresearch employed a descriptive qualitative approach, with data collected throughobservation, interviews, questionnaires, and documentation. Data validity wasensured through triangulation of techniques and sources, and the analysisfollowed Miles and Huberman’s model, which includes data reduction, datadisplay, and conclusion drawing. The findings show that the use of comics basedon the Pancasila Student Profile values significantly improved students’ readingliteracy. Approximately 70.06% of students met the literacy indicators, whichinclude literal, critical, and creative reading skills. However, 29.94% of studentshad not yet achieved optimal progress, especially in terms of reading interest. Withappropriate teacher guidance, comics can serve as an effective tool to fosterreading interest and enhance literacy skills in accordance with the developmentalstage of elementary school students.